2006
DOI: 10.1109/tap.2006.877155
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic scattering from vibrating penetrable objects using a general class of time-varying sheet boundary conditions

Abstract: Abstract-Calculation of electromagnetic (EM) scattering from vibrating penetrable cylinders of arbitrary cross-section is presented using a general class of time-varying sheet boundary conditions (SBCs) in conjunction with the method of moments (MoM). Sheet impedance and admittance expressions are first derived from the exact scattering solution for a penetrable circular cylinder with perturbed radius. Then, using the SBCs, integral equations are derived and solved numerically so that vibrating cylinders with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A common approach to analyzing or simulating such problems involves the use of the quasi-stationary (QS) approximation [18], [19] wherein the scattered field is calculated as if the scattering object were stationary at any instance in time. Our approach for modeling this multi-physics problem with the QS approximation involves two types of numerical simulations.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common approach to analyzing or simulating such problems involves the use of the quasi-stationary (QS) approximation [18], [19] wherein the scattered field is calculated as if the scattering object were stationary at any instance in time. Our approach for modeling this multi-physics problem with the QS approximation involves two types of numerical simulations.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…The challenges of spatially resolving the small tissue displacements in the FDTD grid and accurately calculating the small Doppler component of the scattered field can be overcome by modeling the vibrating object as a stationary object with time-varying sheet boundary conditions (SBCs) [19], [20]. The total scattered field is decomposed into the unperturbed field scattered by the stationary object and a Doppler field perturbation, , associated with the vibration of the object.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…By considering the intrinsic inaccuracies of using numerical techniques, such as the finite-difference-time-domain method (FDTD) and Lorentz precise integration time-domain method (Lorentz-PITD), for a moving object [36][37][38][39][40][41][42], here the STR and Mie theory [43][44][45][46] are employed. Also, other kinds of motions for an individual object such as rotational [47][48][49][50][51] and vibrational [52][53][54] have been investigated, but, here the translational motion is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…As a target undergoes non-uniform motion in addition to its bulk translation, the features produced by SAR images can be useful for target recognition. In addition to the changes in a SAR image, the non-uniform motion-induced Doppler introduces some form of Doppler frequency modulations in the radar signal [6]- [13]. Research studies have found that this micro-Doppler can be extracted by the time-frequency transforms to provide unique features for moving target identification and recognition [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lampropoulos has been invited keynote speaker in major technical events, organized and was General Chair in major multi-society conferences, i.e., International Conference on Applications of Photonic Technology or Photonics North (1994, 1996. 1998, 2002, 2006, 2008, 2009-Vice Chair, 2005 Honorary Chair). He was the General Chairman of the 2009 International Conference on Space Technology held in Thessaloniki, Greece on Aug. 24-26.…”
mentioning
confidence: 99%